Comportamento dos clientes : proposta de um sistema de informação para suporte a tomada de decisão para pequenas e médias empresas comerciais - (:unkn) unknown (Universidade Federal do Pampa, 2022)
For a company, its most valuable assets are its customers. Therefore, understanding customer behavior is fundamental for companies to be able to anticipate their needs, as well as offer a quality service that satisfies their requirements. The company that knows its customer's profile tends to concentrate its efforts in an optimized way, making the best decisions regarding the business. In view of the above, this paper aims to propose the insertion of customer behavioral variables into an Information System, enabling this system to better support the manager, in order to predict customer behavior. To this end, a literature search was conducted in order to deepen the knowledge about customer behavior in small and medium-sized commercial companies, identifying the several variables that may influence the purchase process. Then, a survey was conducted with entrepreneurs and managers of companies in the commerce sector, using the Delphi method, aiming to validate and obtain consensus among the behavioral variables found in the literature survey. After this research, the proposal of an Information System that contemplates the variables that obtained consensus in the Delphi was elaborated, and then a customer survey was applied to track and explore the variables that most impact their buying behavior. Finally, an algorithm capable of predicting customer preferences was used, with the purpose of providing information to support the decision making process of managers. Thus, this study has met all its objectives, contributing to the observation of the importance of knowing the customer's profile, as well as their behavior and consumption habits. In addition, the study can serve as a source for future research on the topics discussed, providing support for the decision making process of entrepreneurs and managers.
Keywords: Comportamento do cliente; Pesquisa bibliográfica; Sistema de informação; Técnica Delphi; Tomada de decisão; Customer behavior; Bibliographic research; Information system; Delphi technique; Decision making; CNPQ::ENGENHARIAS